1994
DOI: 10.1143/jjap.33.6611
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductivity of Ultrathin Zinc Oxide Films

Abstract: Electrical and photoelectrical properties of nondoped and doped zinc oxide films coated on glass plates by the dip-coating method are investigated at room temperature in various ambient atmospheres. The dark conductivity of the nondoped films exponentially decreased with decreasing film thickness while the conductivity under illumination of 350 nm light was almost constant at 100 S·cm-1 irrespective of the film thickness. Consequently thinner films showed larger photoresponse than thicker films.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
175
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(195 citation statements)
references
References 8 publications
17
175
0
Order By: Relevance
“…Schematics of the NW energy band diagrams in dark and under illumination are displayed in parts b and c of Figure 2, respectively, illustrating the charge separation process of photogenerated electrons and holes under the intrinsic NW electric field and the occupation of surface states by photogenerated holes. In ZnO, it has been previously shown that the following trapping mechanism is governing the photoconduction in thin films 25 and NWs: 8,9,13,18,[26][27][28] in the dark (Figure 2b), oxygen molecules are adsorbed on the oxide surface and capture the free electrons present in the n-type oxide semiconductor [O 2 …”
mentioning
confidence: 99%
“…Schematics of the NW energy band diagrams in dark and under illumination are displayed in parts b and c of Figure 2, respectively, illustrating the charge separation process of photogenerated electrons and holes under the intrinsic NW electric field and the occupation of surface states by photogenerated holes. In ZnO, it has been previously shown that the following trapping mechanism is governing the photoconduction in thin films 25 and NWs: 8,9,13,18,[26][27][28] in the dark (Figure 2b), oxygen molecules are adsorbed on the oxide surface and capture the free electrons present in the n-type oxide semiconductor [O 2 …”
mentioning
confidence: 99%
“…decrease in oxygen binding energy. This chemisorption effect on the surface of the films is negligible in the other ambient such as high vacuum, inert gases and nitrogen [26,27].…”
Section: Structural Propertiesmentioning
confidence: 94%
“…After heat treatment, the changes in resistivity of GZO film can be explained by the chemisorptions of oxygen species at the grain boundaries. In general, the chemisorption of oxygen species at the grain boundaries may act as trapping sites and form potential barriers [29] and thereby decrease in the carrier concentration. On the other hand, the oxygen species scatter along the grain boundaries and occupy the oxygen vacancies in the film.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…The conductivity of ZnO is extremely sensitive to UV light exposure. Basically, the photosensitivity in ZnO is regulated by chemisorption of oxygen [15][16][17][18][19]. In the absence of UV light, oxygen molecules get adsorbed on the surface as negatively charged ions by confining the free electrons, thereby create a depletion layer with low conductivity near the surface:…”
Section: Uv Detection Mechanism Of Zno Thin Films and Nanostructuresmentioning
confidence: 99%
“…In addition, outstanding physical and chemical properties of ZnO nanostructures such as large surface area, radiation hardness [12], superior spatial resolution [13] and high electron mobility provide a platform for versatile applications such as in food processing, sterilization of medical equipment, research laboratories, semiconductor processing industry etc., where an installation of UV detector is highly required. In addition, ZnO is also highly desired for thin film transistors, light emitting diodes, solar cells, surface acoustic wave and energy harvesting devices [14][15]. Herein, synthesis of ZnO thin films/nanostructures and study of their UV detection behavior were systematically carried out.…”
Section: Introductionmentioning
confidence: 99%